1.3 μm dissipative soliton resonance generation in Bismuth doped fiber laser - Ahmad, Harith; Aidit, Siti Nabila; Ooi, Shok Ing; Samion, Muhamad Zharif; Wang, S.; Wang, Yu; Sahu, Jayanta Kumar; Abdul Kadir@Jaafar, Muhammad Zamzuri (Natures, 2021)
In this work, a Figure-9 (F9) bismuth-doped fiber laser (BiDFL) operating in the dissipative soliton resonance (DSR) regime is presented. The 1338 nm laser used a BiDF as the active gain medium, while a nonlinear amplifying loop mirror (NALM) in an F9 configuration was employed to obtain high energy mode-locked pulses. The wave breaking-free rectangular pulse widened significantly in the time domain with the increase of the pump power while maintaining an almost constant peak power of 0.6 W. At the maximum pump power, the mode-locked laser delivered a rectangular-shaped pulse with a duration of 48 ns, repetition rate of 362 kHz and a radio-frequency signal-to-noise ratio of more than 60 dB. The maximum output power was recorded at around 11 mW with a corresponding pulse energy of 30 nJ. This is, to the best of the author’s knowledge, the highest mode-locked pulse energy obtained at 1.3 μm as well as the demonstration of an NALM BiDFL in a F9 configuration